2019
DOI: 10.3892/mmr.2019.9885
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‑135a regulates Hut78 cell proliferation via the GATA‑3/TOX signaling pathway

Abstract: The present study investigated the role of microRNA-135a (miR-135a) in cutaneous T-cell lymphoma (CTCL) proliferation. Compared with the normal T lymphocyte control cell line, the mRNA and protein levels of GATA binding protein 3 (GATA-3) were markedly increased in the Hut78 cell line and miR-135a was markedly decreased (P<0.05). Based on bioinformatics, the target gene of miR-135a was identified as GATA-3. Dual luciferase and pre-miR-135a assays showed that miR-135a regulated the translation of GATA-3. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Thus, we speculate that it is important to analyze the post-transcriptional regulation such as suppressive microRNA expression for understanding their molecular mechanisms ( Dinh et al, 2014 ; Melo et al, 2019 ; Bolandi et al, 2020 ). For example, the previous study reported that overexpression of miRNA-135a results in a significant decrease in the expression level of Gata3 protein, even though only minor changes in the Gata3 gene expression is observed ( Wei et al, 2019 ). Also, miRNA-27 and miRNA-128 indirectly regulate stabilities of Gata3 protein after transcription and affect lymphocyte differentiation ( Guerau-de-Arellano et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that it is important to analyze the post-transcriptional regulation such as suppressive microRNA expression for understanding their molecular mechanisms ( Dinh et al, 2014 ; Melo et al, 2019 ; Bolandi et al, 2020 ). For example, the previous study reported that overexpression of miRNA-135a results in a significant decrease in the expression level of Gata3 protein, even though only minor changes in the Gata3 gene expression is observed ( Wei et al, 2019 ). Also, miRNA-27 and miRNA-128 indirectly regulate stabilities of Gata3 protein after transcription and affect lymphocyte differentiation ( Guerau-de-Arellano et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…It acts as an oncogene or tumor suppressor gene to regulate key processes such as tumor proliferation, differentiation, metastasis, apoptosis, and drug resistance. Wei et al 28 reported that miRNA-135a regulates Hut78 cell proliferation through the GATA3/TOX signaling pathway. In recent years, more and more people have realized that miRNA can be used as biomarkers to predict the prognosis and treatment response of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other miRs may play a role in CTCL, including miR-22, miR-135a and miR-223. Diminished expression of miR-135a, miR-223 and miR-22 may allow for the high expression of critical transcription factors including GATA3 as well as growth and proto-oncogenes such as E2F1 and c-Myc, respectively, collectively contributing to CTCL pathogenesis and progression [42,91,92].…”
Section: Key Tumor Suppressive Mirs Playing a Role In Ctcl Pathogenesismentioning
confidence: 99%